Prevalence, antibiotic resistance, resistance and virulence determinants of Campylobacter jejuni in China: A systematic review and meta-analysis - Zhao Li; Hua Cai; Biyao Xu; Qingli Dong; Kai Jia; Zijie Lin; Xiang Wang; Yangtai Liu; Xiaojie Qin (One Health)
Campylobacter jejuni (C. jejuni) is recognized as a serious food contaminant that extensively results in foodborne diseases. Numerous studies have been conducted on the prevalence and antibiotic resistance of C. jejuni, but there is a lack of comprehensive analysis of published data. This study provides a comprehensive overview of the epidemiology, antibiotic resistance, and virulence determinants of C. jejuni in China through a systematic review and meta-analysis. The prevalence levels of C. jejuni from low to high were the humans (5.2 %, 95 % CI: 4.2–6.4 %), foods (12.5 %, 95 % CI: 9.7–15.6 %), animals (15.4 %, 95 % CI: 13.2–17.6 %), and environment (17.8 %, 95 % CI: 9.7–27.7 %), respectively. Furthermore, C. jejuni exhibits high resistance rates to antibiotics such as cefoperazone, nalidixic acid, ciprofloxacin, cefradine, and tetracycline. The overall multi-drug resistance rate (MDR) of C. jejuni was 72.8 % (95 % CI: 62.4–82.2 %), indicating a serious problem with MDR. The resistance of C. jejuni to most antibiotics has increased in the last 20 years. Among the main resistance determinants of C. jejuni, gyrA_T86I and tet(O) had a higher pooled prevalence of 94.8 % (95 % CI: 88.7–99.0 %) and 79.0 % (95 % CI: 66.9–89.2 %), respectively. Furthermore, the high prevalence of virulence-related genes was shown in C. jejuni, such as adhesion (cadF, racR), invasion (ciaB, iamA, ceuE), and toxin (cdtB, cdtC). In summary, C. jejuni has a high prevalence with regional characteristics, and antibiotic resistance of this bacterium especially animal sources remains a serious problem in China. Comprehensive monitoring and control measures for this pathogen are urgently needed to ensure food safety and public health.